#TITLE_ALTERNATIVE# - HAANS (NIM : 22207007), ARIE
Experimental design methods use to assessing the various source of geology and reservoir uncertainties to study how they affect to determine ultimate recovery and how long plateu gas rate period. Uncertainty of this geology parameter and reservoir need to be studied because of inexistence of data core and SCAL, less wholy data PVT and has just two wells developed at this gas-X field. Thereby study is important done to know level of uncertainty of geology parameter and reservoir at this gas-X field. This study applies design two level fractional factorial and uses method Plackett-Burman to determine level of uncertainty of the parameter. From this study obtained result that level of uncertainty of parameter having an effect on to recovery factor ( RF) from the biggest until smallest is K multiplier, Sgr, Kv/Kh, Krg, Krw, skin factor, aquifer size, porosity, permeability, gas density and IGIP. Meanwhile level of uncertainty of parameter having an effect on to plateu gas rate from the biggest until smallest is K multiplier, Kv/Kh, gas density, Sgr, permeability, porosity, aquifer size, Krg, skin factor, IGIP and Krw.